Globalization, territory and institutions : the case of Barranquilla, Colombia, 1990-2010 (2014)
This paper studies the relationship between globalization and territory from an institutional economics perspective. The goal is to show that the notion of territory as a specific geographic space is an important factor and that territory exists wherever human agency interacts with social, political, institutional and economic structures. From this perspective, we examine the case of Barranquilla, Colombia, to show that cities must not only be close to the sea to take part in the global economy but that ceremonial/instrumental institutional patterns are also important to understand and evaluate the impact of globalization on a specific territory. When several leaders of Barranquilla's social and economic sectors exhibited a clear civic commitment (i.e., when they supported instrumental institutions), the city achieved a good economic performance. The opposite outcome happened when ceremonial features and inadequate institutions had imposed their logic on the city's economy